Steady State Analysis of Self Excited Induction Generator using Artificial Neural Network Technique - Bhatt, Ankit; Samir, Mohamed (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Due to increasing demand of energy and limitation of non-renewable energy sources, the need of efficient use of renewable energy sources is increasing. An Induction Generator with its various advantages such as low cost, simplicity, robust construction, inherent protection against short circuit and absence of dc source for excitation makes it very useful in the renewable energy industry. By connecting capacitors to the stator terminals makes it feasible for Induction Machine to be used as a Self Excited Induction Generator. The ability of an Induction Generator to work as a standalone generator makes it very useful in the generation of electrical energy in remote areas. The main drawbacks of SEIG are poor voltage and frequency regulation. The thesis gives the analysis o Self Excited Induction Generator using artificial intelligence. The proposed ANN model is trained by different set of data obtained from simulation of machine by using MATLAB®/SIMULINK® software. The comparison of calculated and predicted data confirms the validity and accuracy of the proposed work.